Oncogenic Chromatin Modifier KAT2A Activates MCT1 to Drive the Glycolytic Process and Tumor Progression in Renal Cell Carcinoma - Guo, Yuanyuan; Liu, Beibei; Liu, Yihan; Sun, Wei; Gao, Wuyue; Mao, Shilong; Chen, Li (Frontiers in Cell and Developmental Biology, 2021)
Objectives: This study aims to investigate the underlying mechanisms of KAT2A/MCT1 axis in renal cell carcinoma (RCC), providing potential therapeutic targets. Methods: We obtained the expression data of KAT2A and MCT1 from The Cancer Genome Atlas Kidney Clear Cell Carcinoma (TCGA-KIRC) and International Cancer Genome Consortium (ICGC) databases. Differential analysis was conducted via limma package. The CCK8 assay, soft agar assay, clone formation assay and patients-derived organoid models were used to detect cell growth. The transwell and wound-healing assays were utilized to detect cell migration. The in vitro and in vivo assays were further conducted to assess the oncogenic roles of KAT2A. The transcriptome sequencing and chromatin immunoprecipitation (ChIP) sequencing were conducted to screen KAT2A downstream targets. The dose-effect curves were used to detect the 50% inhibiting concentration (IC50) of AZD3965. Data analysis was performed in Graphpad Prism (Version 8.3.0) and R software (Version 3.6.1). Results: Our study found that KAT2A was highly expressed in RCC versus normal samples. Prognostic analysis indicated that high KAT2A was an independent biomarker and associated with poor survival outcomes. KAT2A could promote RCC proliferation and distal metastasis in vitro and in vivo. Transcriptome analysis and ChIP-seq were combined to find that KAT2A mainly regulate glycolytic process. Validation and rescue assays revealed that MCT1 was the downstream target of KAT2A and KAT2A depended on MCT1 to promote RCC malignant phenotypes. Lastly, MCT1 inhibitor (AZD3965) was effective to treat KAT2A-induced RCC progression. Conclusion: Our study indicated that KAT2A was an oncogenic chromatin modifier that promotes RCC progression via inducing MCT1 expression. We proposed that MCT1 inhibitor (AZD3965) was useful for suppressing RCC.